HIRUK PIKUK PERAN DAN FUNGSI DEWAN PENGUPAHAN: Suatu Kajian Terhadap perjalanan Penetapan Upah Minimum Kabupaten (UMK) Kabupaten Mojokerto - santosa, santosa; Wijaya, Dian (MAJAPAHIT POLICY, 2024)
This paper will conduct a criminological study of the determination of the UMK based on the KHL, productivity and taking into account economic growth, which raises problems. First, there is a "push and pull" between workers and employers in calculating a decent UMK; and second, there are demands for an increase in the UMK every year followed by large-scale demonstrations from the district to the provincial level with threats and anarchic actions so that a solution is needed for the determination of the UMK in the future.